In-situ stress and permeability causality model of a low-rank coalbed methane reservoir in southwestern Ordos Basin, China. (18th April 2021) - Lin, Yabing; Qin, Yong; Duan, Zhonghui; Ma, Dongmin; Chen, Long
Abstract: The study of the relationship of in-situ stress and permeability is of great necessity to understand the formation mechanism of high-permeability coal reservoir. However, characteristics of in-situ stress and its relationship with permeability in low-rank CBM blocks of China is poorly understood. This study employs permeability and in-situ stress test experiment to analyze the vertical variation law of in-situ stress and permeability and the control mechanism of in-situ stress on permeability in the Binchang block of southwestern Ordos Basin. It is concluded that the permeability varies from 0.11–6.84 mD, and the entire coal reservoir is in a state of relative tension in the Binchang block. The extended Somerton stress–permeability model composed of six stress parameters and the geological model of in-situ stress–permeability were established. The modeling results indicate that permeability is most sensitive to the maximum horizontal stress and its derived parameters, and least sensitive to vertical stress. This model indicates that highly permeability develop in the two-stage turning burial depth section (480–800 m), which is consistent with the minimum value of stress parameters such as the lateral pressure coefficient, which indicate that the relative tension stress zone in the depth profile provides structural conditions that are conducive to the development of permeability.